Evaluation of Polyphenol Intake in Pregnant Women from South-Eastern Spain and the Effect on Anthropometric Measures at Birth and Gestational Age - Hinojosa-Nogueira, Daniel; Romero-Molina, Desirée; Gonzalez Alzaga, Beatriz; Giménez-Asensio, María José; Hernández, Antonio F.; Navajas Porras, Beatriz; Delgado-Osorio, Adriana; Gómez-Martín, Antonio; Pérez-Burillo, Sergio; Pastoriza, Silvia; Lacasaña, Marina; Rufián-Henares, José Ángel (MDPI, 2024)
During pregnancy, controlling nutrition is crucial for the health of both mother and foetus. While polyphenols have positive health effects, some studies show harmful outcomes during pregnancy. This study evaluated polyphenol intake in a cohort of mother–child pairs and examined its effects on foetal anthropometric parameters. Polyphenol intake was assessed using food frequency questionnaires (FFQs) and 24-h dietary recalls, and analysed with the Phenol-Explorer database. Gestational age and birth measurements were retrieved from medical records. Statistical analyses validated dietary records and assessed polyphenol impact using multivariate generalised linear models. The study found that mean gestational age was 39.6 weeks, with a mean birth weight of 3.33 kg. Mean total polyphenol intake by FFQ was 2231 mg/day, slightly higher than 24-h recall data. Flavonoids and phenolic acids constituted 52% and 37% of intake, respectively, with fruits and legumes as primary sources. This study highlights the use of FFQs to estimate polyphenol intake. Furthermore, the study found associations between polyphenol consumption and anthropometric parameters at birth, with the effects varying depending on the type of polyphenol. However, a more precise evaluation of individual polyphenol intake is necessary to determine whether the effects they produce during pregnancy may be harmful or beneficial for foetal growth.
Keywords: Polifenoles; Embarazo - Aspectos nutricionales; Embarazadas; Foetal anthropometry; Polyphenols; Pregnant women; 24 hours dietary recalls; Food frequency questionnaire